Religiusitas dan Agresivitas Siswa SMA X Banjarmasin - Akhmad Rozali; Shanty Komalasari (Jurnal Studia Insania, 2021)
An environment with a high crime will potentially affect student aggression. One way to reduce aggressiveness is to instil religious values through learning at school. However, religious learning in schools is still relatively minimal. The purpose of this study was to determine the correlation between religiosity and student aggressiveness. The population in this study was 214 students, with a sample of 60 students from SMA X in Banjarmasin. The sample in this study was taken by probability sampling technique. The data collection instrument uses a Likert model scale, and data analysis uses Product Moment correlation with the help of SPSS for window 21. Based on the calculation results, it is known that there is a significant negative correlation (-0.451) between religiosity and aggressiveness, so that the higher the student's religiosity, the lower the aggressiveness: students or vice versa.